Political bias indicators and perceptions of news - Bruchmann, Kathryn; Vincent, Subramaniam; Folks, Alexandra (Frontiers in Psychology, 2023)
Introduction Recently, a variety of political bias indicators for social and news media have come to market to alert news consumers to the credibility and political bias of their sources. However, the effects of political bias indicators on how people consume news is unknown. Creators of bias indicators assume people will use the apps and extensions to become less biased news-consumers; however, it is also possible that people would use bias indicators to confirm their previous worldview and become more biased in their perceptions of news. Methods Across two studies, we tested how political bias indicators influence perceptions of news articles without partisan bias (Study 1, N = 394) and articles with partisan bias (Study 2, N = 616). Participants read news articles with or without political bias indicators present and rated the articles on their perceived political bias and credibility. Results Overall, we found no consistent evidence that bias indicators influence perceptions of credibility or bias in news. However, in Study 2, there was some evidence that participants planned to use bias indicators in the future to become more biased in their future news article selection. Discussion These data shed light on the (in) effectiveness of interventions against blindly consuming biased news and media.